Prevalence of Cervicalgia and Its Association with Gender, Years of Practice and BMI Among Dentists: A Cross-Sectional Study: Prevalence of Cervicalgia among Dentists - Anjum, Hadia; Farooq, Jizza; Baloch, Mahnoor; Shahid, Areeba; Baig, Unzillah; Ayub, Humera (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
Cervicalgia, is a common occupational hazard in dentistry due to the prolonged, stooped posture maintained during clinical procedures. Objective: To determine the prevalence of cervicalgia among dentists and explore its association. With gender, Body Mass Index (BMI), and years of clinical practice. Methods: This cross-sectional study was conducted using the Neck Disability Index (NDI) questionnaire. A sample of 147 dentists was selected through convenience sampling, with data collected from Pakistan Institute of Medical Sciences (PIMS), School of Dentistry (SOD), and Islamabad Dental Hospital (IDH). Data were analyzed using SPSS version 25.0, applying the chi-square test to evaluate associations between NDI scores and the study variables. Results: Out of 147 participants, 82 (55.8%) reported experiencing neck pain, while 65 (44.2%) did not. Statistical analysis revealed significant associations between the total NDI score and BMI, years of clinical practice, and presence of neck pain (p<0.05). Conclusions: Cervicalgia is highly prevalent (55.8%) among dental professionals and is significantly associated with higher BMI and clinical experience. It poses a substantial impact on daily functioning, underscoring the urgent need for ergonomic interventions and preventive strategies such as regular physical activity and posture correction to reduce its onset.